Primary school teachers’ opinions about the institution of school advisor - Μαυρίδης, Ελευθέριος (Education Sciences, 2019)
School advisor is one of the most important institutions in Greek educational system with variety of competences. Thesis propose is the primary education educators views survey about the school advisor institution. Get used descriptive quantitative survey method and data collection was performed by questionnaire as survey tool. Survey matters are connected with questionnaire connectional categories and relate to the school advisor role in education system, the selection procedure and criteria, the participation in educator evaluation, the cooperation with educator in classroom, the contribution about the educator training and also the institution future form. Survey conducted in Central Macedonia with 203 primary teachers, preschool teachers and specialized teachers. The survey results show that the school advisor institution is accepted by the primary education educators, nevertheless they deliver complaints and modifications need about some operation points.